Acute Cytotoxic Cerebellar Edema Subsequent to Fentanyl Patch Intoxication in an Infant - Lindsey N. Haut; Rupa Radhakrishnan; Riad Lutfi; Louise W. Kao; Laurie L. Ackerman (Case Reports in Critical Care)
The opioid epidemic continues to have devastating consequences for children and families across the United States with rising prevalence of opioid use and abuse. Given the ease of access to these medications, accidental ingestion and overdose by children are becoming increasingly more common. The recognition of opioid-induced neurotoxicity and the associated life-threatening complication of acute cerebellar cytotoxic edema are crucial, as are the high morbidity and mortality without timely intervention. We discuss an infant with acute cytotoxic cerebellar edema following mucosal exposure to a transdermal fentanyl patch.